Contrasted resistance and resilience of two mangrove forests after exposure to long-term and short-term anthropic disturbances. (April 2019) - Capdeville, C.; Abdallah, K.; Walcker, R.; Rols, J.L.; Fromard, F.; Leflaive, J.
Abstract: Mangroves, coastal forests under the influence of tides, are known to be very resilient when they face natural disturbances such as storms or tsunami. While they provide several ecological services, they are threatened by many anthropic pressures. The aim of this study was to assess and to compare the stability of two mangrove fringes defined by contrasted set of natural constraints and exposed to pretreated domestic wastewaters discharges. The in situ experimental system set up in Mayotte Island (Indian Ocean) allowed us to determine both the short-term (2 years) and the long-term (9 years) resistance and the resilience. We focused on vegetation and crabs, an essential component of mangroves fauna. Wastewater discharges induced increases in tree coverage, leaves productivity and pigment content, and a decrease in crab diversity and density. Within 2 years after the release of the disturbance, several parameters reach back control values indicating fast resilience. Our results notably emphasized the high stability of the mangrove fringe dominated by Rhizophora mucronata trees, which was both more resistant and more resilient. This makes this fringe more suitable for application purposes, such as outfall for domestic wastewaters treatment plants. Highlights: The stability (resistance and resilience) of two mangrove zones was studied. Mangroves were exposed at short and long term to anthropogenic disturbance. Vegetation growth was enhanced and crab populations were rapidly modified. Crab and vegetation showed partial resilience within 2 years. One zone was much more stable than the other one.